2021
DOI: 10.1097/mcp.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Emerging clinical perspectives in cystic fibrosis liver disease

Abstract: Purpose of reviewLiver disease (CFLD) as a complication of cystic fibrosis is recognized as a more severe disease phenotype in both children and adults. We review recent advances in understanding the disease mechanism and consider the implications of new strategies for the diagnosis and management of cystic fibrosis in those with evidence of clinically significant liver disease.Recent findingsEvidence suggests that the prevalence of CFLD has not declined with the introduction of newborn screening. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…13 Interestingly, the prevalence of CFLD has not decreased with the introduction of newborn screening in high income countries. 15 Our study was focused on evaluating the prevalence of CFLD, and risk factors that contribute to the development of CFLD in a low-middle income countries (LMIC) like Egypt. The occurrence of CFLD in a prospective study was found to be 2.5 per 100 patient-years during early life years, with an increase in the second decade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Interestingly, the prevalence of CFLD has not decreased with the introduction of newborn screening in high income countries. 15 Our study was focused on evaluating the prevalence of CFLD, and risk factors that contribute to the development of CFLD in a low-middle income countries (LMIC) like Egypt. The occurrence of CFLD in a prospective study was found to be 2.5 per 100 patient-years during early life years, with an increase in the second decade.…”
Section: Discussionmentioning
confidence: 99%
“…Improving life expectancy in pwCF in high income countries is associated with emergence of CFLD with incidence of 10%−15% 13 . Interestingly, the prevalence of CFLD has not decreased with the introduction of newborn screening in high income countries 15 . Our study was focused on evaluating the prevalence of CFLD, and risk factors that contribute to the development of CFLD in a low‐middle income countries (LMIC) like Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Historical post-mortem studies highlighted the propensity of CF to affect the liver with more than 70 % of PwCF showing evidence of focal biliary cirrhosis [ 4 ]. CFLD is most likely a complex, multi-faceted disease with multiple causative pathologies, including biliary fibrosis, obliterative portal venopathy and nodular regenerative hyperplasia [ 5 , 6 ]. These can be simultaneously active but their contribution to disease may vary between individuals and over time in the same person.…”
Section: Introductionmentioning
confidence: 99%
“…Promisingly, LSM by TE in CFLD, has been shown to correlate with biochemical and USS evidence of CFLD [ 15 , 20 , 22 , 23 ]. However, there has been no consensus agreement on a diagnostic value in PwCF [ 24 ].…”
Section: Introductionmentioning
confidence: 99%